Menemukan Ikigai: Merancang Masa Depan Dengan Passion Dan Potensi - Hasanah, Yulia Nur; Suprayogi, Yogi; Rizaldi, Fikri Mohamad (Apik Cahaya Ilmu, 2025)
This community service program aims to help Darul Hikam High School students in finding Ikigai, a Japanese concept which means